Merubah Budaya Pelayanan Publik: Adopsi dari Sistem Informasi Manajemen Perizinan Mobile Elektronik (Simolek) - Sari, Fara Merian; Yandra, Alexsander (Sosial Budaya, 2023)
This research examines the adoption of SIMOLEK in changing the culture of public services. Licensing and non-licensing services at the Investment and One-Stop Integrated Service Office of Pekanbaru City use the SIMOLEK application as a medium to facilitate service access. However, problems arise when the infrastructure in the application is not supportive, such as wifi errors or unstable data networks in cards that have implications for the processing process slowing down. Finally, people who are processing their business licenses still have to come to the Pekanbaru City Investment and One-Stop Integrated Service Office. By coming to the location, the government's readiness to change the culture of public services looks mature in planning but mental in implementation.  The method used in this research is through descriptive analysis which seeks to describe existing data from various sources and relate it to social phenomena and trace all the facts related to the problem of this title.The theory used in this research is Rogers' theory. The results show that the adoption of SIMOLEK has not been optimally implemented in changing the service culture but SIMOLEK is believed to be able to change the service culture from conventional face-to-face to online service processes